Educação, política e colonização : processos pedagógicos não formais na Região do Alto Uruguai/RS no início do século XX - Beatrici, Rodrigo Ferronato (2012)
The present work has as an object of search to the region of Alto Uruguay in the first two decades of the twentieth century. In this space and time, we seek to develop some pedagogical reflections on informal educational processes, linked to relations of domination intrinsic to the official colonization project planned by the State. This is a bibliographical and documentary research, and between methodological approaches, we chose to dialectic. Reading and writing were constructed from local history of inter-relating it with the overall interpretation of an effort in, the place where it is replaced by importance (SANTOS, 2006, p. 10). In addition to the analysis, some categories are used, among which there are: education, space, experience, culture, progress, territory - deterritorialization - repossession, social class, civil society and political society. The central problem of research is in the process of deterritorialization / reterritorialization was realized when the project of colonization in the region of Alto Uruguay, where he formed systems of inequality and exclusion in relation to subordinate groups. In developing the survey, the thread was formed around the understanding that education, within the project of colonization, there was an education as the practice of freedom. The research is structured in two main axes. The first axis turns to the historical evidence about the changes caused by the expansion of capitalism in the countryside. The second axis, in turn faces a pedagogic analysis of events related to these changes